Unlocking the bacterial membrane as a therapeutic target for next-generation antimicrobial amphiphiles. (October 2021) - Mehta, Devashish; Saini, Varsha; Aggarwal, Bharti; Khan, Ali; Bajaj, Avinash
Abstract: Gram-positive bacteria like Enterococcus faecium and Staphylococcus aureus, and Gram-negative bacteria like Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter Spp . are responsible for most of fatal bacterial infections. Bacteria present a handful of targets like ribosome, RNA polymerase, cell wall biosynthesis, and dihydrofolate reductase. Antibiotics targeting the protein synthesis like aminoglycosides and tetracyclines, inhibitors of RNA/DNA synthesis like fluoroquinolones, inhibitors of cell wall biosynthesis like glycopeptides and β-lactams, and membrane-targeting polymyxins and lipopeptides have shown very good success in combating the bacterial infections. Ability of the bacteria to develop drug resistance is a serious public health challenge as bacteria can develop antimicrobial resistance against newly introduced antibiotics that enhances the challenge for antibiotic drug discovery. Therefore, bacterial membranes present a suitable therapeutic target for development of antimicrobials as bacteria can find it difficult to develop resistance against membrane-targeting antimicrobials. In this review, we present the recent advances in engineering of membrane-targeting antimicrobial amphiphiles that can be effective alternatives to existing antibiotics in combating bacterial infections. Graphical abstract: Image 1